2014
DOI: 10.1167/iovs.13-12714
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics, Alterations, and Consequences of Minimally Invasive Intraocular Pressure Elevation in Rats

Abstract: After accurate IOP elevation with minimally invasive methods, it was possible to detect RGC loss and retinal thinning. While suction cup is capable of simulating accurate arbitrary IOP profiles, loop adjustment enables the detection of pressure-dependent retinal alterations. For the first time, it was feasible to investigate consequences of variable IOP elevation profiles, including pressure peaks, by using real-time live imaging in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
1
18
0
2
Order By: Relevance
“…Optic nerve neurodegeneration was accessed after p-phenylenediamine (PPD) staining of 0.7 µm semithin transverse optic nerve sections as described previously 55 . Briefly, six to seven images per optic nerve were captured in a crosswise procedure using 100x magnification (Olympus SPlan 100x/1.25 oil, 160/0.17, Olympus Deutschland GmbH, Hamburg, Germany) and an upright microscope (Olympus Vanox-T AH-2;) in accordance with a consistent orientation.…”
Section: Methodsmentioning
confidence: 99%
“…Optic nerve neurodegeneration was accessed after p-phenylenediamine (PPD) staining of 0.7 µm semithin transverse optic nerve sections as described previously 55 . Briefly, six to seven images per optic nerve were captured in a crosswise procedure using 100x magnification (Olympus SPlan 100x/1.25 oil, 160/0.17, Olympus Deutschland GmbH, Hamburg, Germany) and an upright microscope (Olympus Vanox-T AH-2;) in accordance with a consistent orientation.…”
Section: Methodsmentioning
confidence: 99%
“…(Yang et al, 2012b) Gramlich et al found after chronic recurrent episodes of a short-duration IOP “spike” (1 hour each to 30–35 mmHg), there was a decline in total retinal thickness measured by SDOCT and RGC density measured histologically as well as an increase in the optic nerve axon damage grade. (Gramlich et al, 2014) Using longitudinal SDOCT imaging, Abbott et al found that RNFL loss occurred earlier and was more severe in older rats age 9.5-months as compared with younger rats aged 2-months despite similar exposure to chronic IOP elevation over 3-weeks. Abbott et al also reported that axonal transport disruption and optic nerve damage were substantially worse than RNFL thinning, especially in the older rats and confirmed by post mortem microscopy of retinal whole mounts that there was relative preservation of the intraretinal portion of RGC axons.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 This minimally invasive technique employed the concept of oculopression to produce elevated IOP. [10][11][12] An advantage of the suture compression model is that it is not associated with ocular tissue penetration or traumatization, and therefore relatively preserves the immune privilege of the eye. It was reported that a mild, chronic IOP elevation was induced for at least 15 weeks following an initial IOP spike that appeared immediately after suture placement.…”
mentioning
confidence: 99%